2021
DOI: 10.11604/pamj.2021.38.77.21484
|View full text |Cite
|
Sign up to set email alerts
|

Les infections ostéo-articulaires chez les drépanocytaires à Lubumbashi: étude épidémiologique, étiologie et prise en charge

Abstract: Introduction les complications infectieuses constituent la première cause de morbi-mortalité chez le drépanocytaire surtout avant l´âge de 5 ans. Le but de cette étude est de ressortir les aspects épidémiologiques, les étiologies et la prise en charge des infections ostéo-articulaires chez les drépanocytaires à Lubumbashi. Méthodes il s´agissait d´une étude descriptive transversale et rétrospective réalisée au centre de recherche de drépanocytose de Lubumbashi (CRDL) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…While preventive antibiotic therapy with penicillotherapy has proved effective, vaccination remains the principal means of control [14]. Salmonella typhi, found in coprocultures in this study, is more likely to be implicated in osteoarticular infections [15]. According to the authors, this could be explained by their high susceptibility to osteoarticular infections.…”
Section: Bacteriologymentioning
confidence: 61%
“…While preventive antibiotic therapy with penicillotherapy has proved effective, vaccination remains the principal means of control [14]. Salmonella typhi, found in coprocultures in this study, is more likely to be implicated in osteoarticular infections [15]. According to the authors, this could be explained by their high susceptibility to osteoarticular infections.…”
Section: Bacteriologymentioning
confidence: 61%
“…[4,5] . It constitutes a rare pathology throughout the world according to published articles and in a recent study carried out in our community on bone and joint infections in sickle cell patients in Lubumbashi, Manix et al [6] adds to Almeida [7] and Fatima-Zahrae Bennis [8] had found that bone damage represented 70.87% and came in third place after respiratory and otolaryngological damage; bone pathology is very common in sickle cell patients and is dominated by two major entities: Infarction and infection, infarction being much more frequent (about a ratio of 50/1) [6] . This thesis is affirmed by many authors, that the main orthopedic manifestations in sickle cell patients are osteonecrosis, osteomyelitis, septic arthritis and bone infarction [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Al-Salem and Nasserullah reported on the risks of different hemoglobin phenotypes (HbSS, HbAS and HbAA) developing osteomyelitis in Saudi Arabia. 9,10 They concluded that osteomyelitis in the HbSS population occurred in a frequency of 15 times greater compared with the general population. 9 Additionally, there was a trend of increased risk in the HbSA population; however, there is limited data confirming these results.…”
mentioning
confidence: 99%
“…9,10 They concluded that osteomyelitis in the HbSS population occurred in a frequency of 15 times greater compared with the general population. 9 Additionally, there was a trend of increased risk in the HbSA population; however, there is limited data confirming these results.…”
mentioning
confidence: 99%